(untitled) (Journal Of Educational and Psychological Researches, 2019)
Abstract The current research aims to construct a scale for the nine types of students’ personality according to Rob Fitzel model. To do this, (162) items were formed that present the nine types of personality with (18) items for each type. To test the validity of the scale, a sample of (584) students of Al-Mustansrya University were chosen. The data of their responses was analyzed by using factor analysis. The findings explored (9) factors as one factor for each type of personality with (12) items for each one. Then, the reliability of the scale was found by using the test-retest method and Alfa Cronbach method.